Radegund the trials and triumphs of a Merovingian queen - Dailey, E. T. (Women in Antiquity, 2023)
"Radegund: The Trials and Triumphs of a Merovingian Queen is a biography of a sixth-century princess, war captive, queen, deaconess, nun, and saint. This book examines her life, times, and legacy, illuminating the society in which she lived and narrating her personal history in an accessible way, appealing to a general audience, yet without compromising its merit as a work of scholarship that offers important new insights for experts in the field. Radegund succeeded in establishing a place for herself within this difficult and dangerous world, despite the trials she faced, which distinguishes her as a figure worthy of detailed biographical study. Unique among her peers, Radegund achieved a position of prominence as a woman in a foreign land, without resorting to the violence, intrigue, and murder that characterised the lives of other prominent women during this period, like Brunhild or Fredegund. Departing from the portrait of an idealised saint offered by her early medieval hagiographers, and from the traditional narrative established in more recent academic works, this book presents a new interpretation of this remarkable woman with many insights about the history of a crucial period in the transition from Roman to medieval epochs"--